Inhibiting the Production of Polychlorinated Organic Pollutants in the Hydrolysis Oxidation Process of 1,2-Dichlorobenzene - Yuqing Li; Bisi Lv; Na Li; Yingjie Li; Wenjie Song; Jiahui Zhou (Atmosphere, 2025)
The hydrolysis oxidation of 1,2-chlorobenzene (1,2-DCB) over Pd-Ti-Ni/ZSM-5(25) catalysts has been investigated as a safe and environmentally friendly method for the removal of chlorinated aromatic organic compounds. Experimental results demonstrate that hydrolysis oxidation technology can effectively suppress the formation of polychlorinated organic compounds. Among the catalysts studied, the 0.5%Pd-2%Ti-8%Ni/ZSM-5(25) catalyst exhibited optimal hydrolysis oxidation performance, achieving complete conversion of 1,2-DCB at 425 °C. Notably, this technology significantly inhibits the formation of polychlorinated organic by-products during the catalytic degradation of 1,2-DCB. Although trace amounts of chlorobenzene were still detected, the overall reduction in hazardous by-products is remarkable. Characterization techniques, including X-Ray Diffraction (XRD), X-Ray Photoelectron Spectroscopy (XPS), Pyridine adsorption infrared Spectroscopy (pyridine IR) and Fourier transform infrared spectroscopy (FT-IR) analysis, revealed that the acidity and redox properties of the catalyst surface play a pivotal role in the hydrolysis oxidation process. The hydrolysis oxidation of chlorinated volatile organic compounds not only effectively reduces pollutant concentrations but also prevents the generation of more toxic by-products. This dual benefit not only protects the environment but also minimizes ecological risks, highlighting the potential of this technology for sustainable environmental remediation.